Astrophysical interpretation of Pierre Auger Observatory measurements of the UHECR energy spectrum and mass composition - Condorelli Antonio (EPJ Web of Conferences, 2023)
We present a combined fit of a simple astrophysical model of Ultra-high-energy cosmic-ray sources to both the energy spectrum and mass composition data measured by the Pierre Auger Observatory. The astrophysical model we adopted consists of identical sources uniformly distributed in a comoving volume, where nuclei are accelerated with a rigidity-dependent mechanism. The fit has been performed at first for energies above 5 EeV, i.e., the region of the all-particle spectrum above the so-called “ankle” feature, and has then been extended to lower energies in order to include this feature. The fit results and their astrophysical implications in both cases are discussed.